Leaf gas exchange in cowpea and CO2 efflux in soil irrigated with saline water - Wanderson J. de Oliveira; Edivan R. de Souza; Jailson C. Cunha; Ênio F. de F. e Silva; Venâncio de L. Veloso (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Leaf gas exchanges in plants and soil respiration are important tools for assessing the effects of salinity on the soil-plant system. An experiment was conducted with cowpea irrigated with saline water (0, 2.5, 5.0, 7.5, 10.0 and 12.5 dS m-1) prepared with two sources: NaCl and a mixture of Ca, Mg, Na, K and Cl ions in a randomized block design and a 6 x 2 factorial scheme, with four replicates, totaling 48 experimental plots. At 20 days after planting (DAP), plants were evaluated for net photosynthesis (A), stomatal conductance (gs) and transpiration (E) using the Infra-Red Gas Analyzer (Model XT6400- LICOR), and water use efficiency, intrinsic water use efficiency and instantaneous efficiency of carboxylation were calculated. At 60 DAP, the soil CO2 efflux (soil respiration) was determined with a camera (Model 6400-09- LICOR). Salinity caused reductions in A, gs and E. However, the salt source did not have significant effect on these variables. Soil CO2 efflux was reduced with the increase in the electrical conductivity, especially in the mixture of ions.